PENGARUH KOMUNIKASI INTERNAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PUSKESMAS CICINDE KECAMATAN BANYUSARI KABUPATEN KARAWANG - Wanta; Mozaiq Nur Ramadan Saleh; Hidayaty, Dwi Epty (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The Performance of the Cicinde Community Health Center employees during the observation period appeared to be less than optimal. This can be seen from the performance results data for 2022-2023 attached. The research aims to determine employee performance which can be influenced by internal communication, employee performance which can be influenced by organizational culture and determine the simultaneous influence of both. This research uses quantitative methods with a descriptive verification approach with multiple linear regression analysis techniques with the SPSS 27 analysis tool. Research data uses primary and secondary data, obtained from questionnaires distributed to respondents, while secondary data comes from departmental documents and related publications. The partial research results for the two independent variables are that there is no significant effect on the dependent variable. Meanwhile, the research results can simultaneously influence employee performance positively and significantly. The implications of this research can help Puskesmas management in improving performance effectiveness through improving internal communication and a strong organizational culture. This research also contributes to understanding the factors that influence employee performance in health institutions.